β-Change of Riemannian Space and Special Cases of one-form β - Mandal, Khageshwar (Journal of Nepal Mathematical Society, 2018)
In this paper, we consider β-change of Finsler metric L given by L = f(L; β), where f is any positively homogeneous function of degree one in L and β. The objectives of the paper are to obtain the β-change of a Riemannian space, projective change of Finsler metric and to discuss the special cases of one-form β.